(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Data about new for Ukraine lichenicolous fungus Phoma cladoniicolaDiederich,Kocourk. & Etayo are reported. It was found on sand dunes in the Lower Dnieper (Kherson region, Ukraine). The fungus causes the disease with mosaic dying off of lichen thallus in Cladoniaphomosis. one of dominant species of the biological crust in the sand-dunes ecosystems of Lower Dnieper. The lichenicolous fungus is found on C. arbuscula, C. subrangiformiand C. subulatafor the first time.